PUNISHMENT SYSTEM POLICY IN THE PREVENTION EFFORT TO CRIMINAL ACT OF MURDER (CASE STUDY OF MURDER UNDER DRUNKENNESS) - Bambang Hartono; Benny Karya Limantara (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Research on punishment system policy in the prevention effort to criminal act of murder (case study of murder under drunkenness) which aims to answer problems about: (1) How punishment system policy to criminal act of murder which is currently at? (2) How punishment system policy to the criminal act of murder in the future? This research uses a juridical-normative as the main approach and comparative approach, namely the punishment system policy to the criminal act of murder (case study of murder under drunkenness) that exist in the Criminal Code with that is in the concept of the Criminal Code and also comparison problems the criminal act of murder under drunkenness between the concept of the Criminal Code of other countries. Punishment system policy to the criminal act of murder in Criminal Code currently does not mention the issue of commission and omission are clearly so in the punishment matter of criminal act of murder under drunkenness uses of the principle of judge consideration.